Penaatan Atas Perjanjian Multilateral di Bidang Lingkungan Hidup - Ishak, Inar Ichsana (UI Scholars Hub, 2005)
Multilateral treaty in environmental area is one of the international treaty that defined in Convention on the Law of the Treaties, Vienna, 1969 as an international agreement concluded between states in written form and governed by international law, whether embodied in a single instrument or in two or more related instruments and whatever its particular designation. However, international environmental law is tending to be considered as “soft law” rather than “hard law” because its compliance approaches. This article will discuss about the compliance measure from the international point of view because international compliance is based on the balance of advantages and consequences of a state should it participate in MEAs.